Theoretical perspectives: sociology and the conservation of scientific heritage - Magnolo, Stefano; Galán-Pérez, Ana (Frontiers in Sociology, 2024)
The following considerations adopt a critical conservation approach to understanding scientific heritage, particularly its intangible aspects. This heritage includes the intellectual and research legacy, encompassing various forms of communication, with a focus on digital technologies. Conservation methods now play a crucial role in transmitting this intangible heritage, shifting from traditional substance-based care to communication systems and enhancement facilitated by digital humanities. These advancements enable novel experiences and foster new academic and social practices. Interestingly, sociology features prominently in this context. It appears twice: first as a discipline that produces intangible heritage worthy of preservation and communication, and second as a theory for communicating this heritage. Our exploration begins by recognizing the university’s role as a cultural agent engaged in producing and transmitting knowledge. We then delve into the concept of scientific heritage, particularly how the Humanities and Social Sciences preserve their heritage compared to the so-called hard sciences. While we acknowledge the importance of the real impact of these disciplines, our focus is on the formal recognition of their scientific production as cultural heritage. Ultimately, we focus on specific heritage worth preserving and reflect on ways to enhance it in the future.